Beyond Hemoglobin: The Effect of Iron Supplementation on Cognitive Function, Academic Achievement, and School Absenteeism in Anemic Indonesian Adolescents – A Randomized Controlled Trial - Dewi, Yulia Ratna; Emma Ismawatie; Yulita Maulani; Eko Sumargiyanto (Sriwijaya Journal of Obstetrics and Gynecology, 2024)
Introduction: Iron deficiency anemia (IDA) is a pervasive public health challenge, affecting over one-third of adolescent girls in Indonesia. While the hematological consequences are known, there is a critical lack of high-quality trial data on the functional impact—including cognition and educational outcomes—in this specific population. Methods: We conducted a 12-week, double-blind, placebo-controlled, parallel-group randomized controlled trial in Klaten, Indonesia. We enrolled 200 anemic (Hemoglobin [Hb] < 12 g/dL) female senior high school students, aged 15-18. Participants were randomized (1:1) to receive either 60 mg of elemental iron (as ferrous sulfate) or an identical placebo, taken daily. Primary outcomes were the change in Hb (hematological) and cognitive processing speed (functional), measured by the Digit Symbol Substitution Test (DSST). Secondary outcomes included anemia prevalence, serum ferritin, academic achievement (change in school-recorded grades), and school absenteeism (days missed). Results: At 12 weeks, the iron group demonstrated a significantly greater increase in mean Hb compared to the placebo group (2.7 g/dL vs. 1.4 g/dL; mean difference: 1.3 g/dL, 95% CI: 0.9-1.7, p < 0.001). Anemia prevalence was halved (20% vs. 40%, p = 0.02). Functionally, the iron group showed a marked improvement in DSST scores (mean change: +8.5 vs. +2.1; mean difference: 6.4, 95% CI: 4.1-8.7, p < 0.001), a significant improvement in academic grades (mean difference: +1.6 points, 95% CI: 0.5-2.7, p = 0.005), and a 61% reduction in mean days of school missed (1.2 vs. 3.1 days; mean difference: -1.9 days, 95% CI: -2.8 to -1.0, p < 0.001). Adverse events were mild and not significantly different between groups. Conclusion: Daily iron supplementation in anemic adolescents robustly improves hematological status and, critically, translates these gains into significant, tangible improvements in cognitive function, academic performance, and school attendance. These findings provide strong, multi-domain evidence to support the scaling of public health anemia interventions.